2000
DOI: 10.4037/ajcc2000.9.3.192
|View full text |Cite
|
Sign up to set email alerts
|

The need to know: experiences of critically ill patients

Abstract: BACKGROUND: Critically ill patients vary in their memories of their experience in the intensive care unit. Some have little recall and need to learn about their critical illness. Others have more vivid memories of their experiences, some of which were extremely unpleasant. Patients' not knowing what was happening may have exacerbated the unpleasant experiences. OBJECTIVES: To elicit the experience of knowing for critically ill patients and to explore the differences in perceptions between patients who were int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
1
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 0 publications
0
37
1
2
Order By: Relevance
“…However, giving the junior nurses the very critically ill patients would be difficult because extra senior support would be needed. Hupcey and Zimmerman (2000) believed that adequate staffing levels were needed to deal with the patients' psychological issues effectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, giving the junior nurses the very critically ill patients would be difficult because extra senior support would be needed. Hupcey and Zimmerman (2000) believed that adequate staffing levels were needed to deal with the patients' psychological issues effectively.…”
Section: Discussionmentioning
confidence: 99%
“…Staff can affect the patients' psychological state; for example, Hupcey and Zimmerman (2000) found patients stated that staff whom they did not know, or in whom they lacked confidence, made them more paranoid and panicky. Swales (1995) demonstrated that nurses find it difficult to talk to unconscious patients and attributed this to the fact that it was a one-way rather than two-way communication process.…”
Section: Termsmentioning
confidence: 99%
“…The Needs of Adult Patients in Intensive Care Unit (NAPinICU) questionnaire was developed and used to carry out this study because there was no validated instrument available for measuring ICU patients' needs. The questionnaire was composed based on the theoretical framework developed from the previous literature: (1) studies about the needs of adult patients in ICUs (Hupcey 2000, Hupcey & Zimmerman 2000, Gonzalez et al 2004, Campbell & Rudisill 2006, Fernandez 2006, Godfrey et al 2006, Santana et al 2007, (2) studies of patients' experiences in adult ICUs (Granberg et al 1998, Novaes et al 1999, Russell 1999, Stein-Parbury & McKinley 2000, McKinley et al 2002, Adamson et al 2004, Rattray et al 2004, Roberts & Chaboyer 2004, Granja et al 2005, Johansson & Fjellman-Wiklund 2005, Lö f et al 2006, Magnus & Turkington 2006, Hofhuis et al 2008 and (3) papers about patientcentred care in adult ICUs (McCauley & Irwin 2006, Davidson et al 2007). Using qualitative inductive content analysis (Elo & Kyngäs 2008), eight categories of needs were identified: the needs (1) for physical comfort, (2) to feel safe, (3) to be respected as a unique individual, (4) for emotional support, (5) to be informed, (6) for privacy, (7) to involve family and friends and (8) to be involved in decisionmaking.…”
Section: Instrumentmentioning
confidence: 99%
“…Unfortunately, there are only a few international studies focusing on the needs of adult patients in ICU (Hupcey 2000, Hupcey & Zimmerman 2000, Gonzalez et al 2004, Campbell & Rudisill 2006, Fernandez 2006, Godfrey et al 2006, Santana et al 2007, remarkably more studies describe patients' experiences (Granberg et al 1998, Novaes et al 1999, Russell 1999, Stein-Parbury & McKinley 2000, McKinley et al 2002, Adamson et al 2004, Rattray et al 2004, Roberts & Chaboyer 2004, Granja et al 2005, Johansson & Fjellman-Wiklund 2005, Lö f et al 2006, Magnus & Turkington 2006, Hofhuis et al 2008). The majority of these studies are qualitative and their generalizability is problematic.…”
Section: Introductionmentioning
confidence: 99%
“…Several interview studies (Bergbom and Askvall, 2000;Hupcey and Zimmerman, 2000;Granberg-Axéll, 2001;Magarey and McCutcheon, 2005) have shown that loved ones have a major impact on patients in an ICU. The loved ones help the patients to remain in touch with reality and give them hope and strength to struggle against critical illness or injuries.…”
Section: Icu Patients' Perspectivementioning
confidence: 99%